Comparison of Gender linguistics in english and uzbek languages (Ta'limning zamonaviy transformatsiyasi, 2024)
The article considers theoretical and methodological aspects of gender linguistics, relevant in the comparative study of English and Uzbek languages. Drawing from sociolinguistic and gender studies perspectives, the research sheds light on the dynamic interplay between language, culture, and gender, offering insights that enhance our understanding of diverse sociocultural constructions of gender identities.В статье рассмотрены теоретические и методологические аспекты гендерная лингвистика, актуальная при сравнительном изучении английского и узбекского языков языки. Опираясь на перспективы социолингвистических и гендерных исследований, исследование проливает свет на динамическое взаимодействие между языком, культурой и полом, предлагая идеи, которые улучшают наше понимание различных социокультурных конструкций гендерной идентичности.Ushbu maqolada ingliz va o'zbek tillarida dolzarb bo'lgan gender tilshunosligi nazariy va metodologik jihatdan ko'rib chiqiladi va qiyosiy tahlil qilinadi. Ijtimoiy lingvistik va gender tadqiqotlari nuqtai nazaridan kelib chiqqan holda, bu maqola til, madaniyat va gender o'rtasidagi dinamik o'zaro ta'sirni yoritib beradi va gender identifikatsiyasining turli xil ijtimoiy-madaniy tuzilmalarini tushunishimizni kuchaytiradigan tushunchalarni taqdim etadi.